2008
DOI: 10.1007/s10560-008-0116-2
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Moderating Influence of Delinquent Peers on the Link Between Trauma, Anger, and Violence Among Male Youth: Implications for Social Work Practice

Abstract: This study's objective was to explore the influence of delinquent peer exposure, on the relationship between male youths' histories of trauma, anger, and violent behavior. Using a nationally representative sample of male adolescents aged 12-17 and self report interviews, information was gathered on their levels of exposure to violence, stressful life events (SLE), anger, depression, delinquent peer exposure, and violent behavior. Results of a moderation analyses revealed that youth who reported higher levels o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 23 publications
1
16
0
1
Order By: Relevance
“…These differences suggest that youth who have experienced traumatic events have more risk factors for offending than do other youth. Although the current study could not evaluate causality, findings are consistent with previous research suggesting that environmental variables and intervening events may influence the relationship between delinquency and trauma (e.g., Maschi and Bradley 2008). Trauma may serve as an indirect risk factor for offending; that is, it may increase the likelihood that other risk factors will occur.…”
Section: Differences By Presence Of Trauma and Trauma Typesupporting
confidence: 86%
See 1 more Smart Citation
“…These differences suggest that youth who have experienced traumatic events have more risk factors for offending than do other youth. Although the current study could not evaluate causality, findings are consistent with previous research suggesting that environmental variables and intervening events may influence the relationship between delinquency and trauma (e.g., Maschi and Bradley 2008). Trauma may serve as an indirect risk factor for offending; that is, it may increase the likelihood that other risk factors will occur.…”
Section: Differences By Presence Of Trauma and Trauma Typesupporting
confidence: 86%
“…Maschi and Bradley (2008) found that negative affect and delinquent peers partially moderated the relationship between traumatic experiences and delinquency. These results highlight, again, the importance of assessing the youth's response to the event (e.g., negative affect) and other environmental influences (e.g., delinquent peers).…”
Section: Introductionmentioning
confidence: 90%
“…Kinship care was more likely to be utilized for females than Non-Kinship care. These findings were supported by, McMillen, Zima, Scott, Auslander, Munson, Ollie, and Spitznagel (2005), which suggested that being male is associated with externalizing problems and lower levels of placement stability (Maschi, & Bradley, 2008). Nevertheless, McMillen et al (2005), in a study of the prevalence of emotional and behavioral problems of adolescents in out-of-home placement, found that males and females did not differ in the frequency in placement stability.…”
Section: Resultsmentioning
confidence: 80%
“…The peer contagion literature suggests that young people in residential facilities with other delinquent youths will have poorer outcomes (Dishion et al, ). Those with severe trauma backgrounds are particularly susceptible to negative influences in groups, as they are more likely to associate with and be affected by delinquent peers (Maschi and Bradley, ; Maschi et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, use of seclusion and restraints, inappropriate use of medications and/or co‐residence with other youth who have been exposed to trauma may add to the problems of young people who already have trauma histories. Young people with traumatic backgrounds are also more likely to associate with and be affected by delinquent peers (Maschi and Bradley, ; Maschi et al, ). Association with delinquent peers is often found to be a significant determinant of offending behaviour (Leve and Chamberlain, ).…”
Section: Introductionmentioning
confidence: 99%